PENEGAKAN HUKUM TERHADAP PELANGGARAN HAK CIPTA MELALUI MEDIA INTERNET - Andi Kurniawati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
This paper presents about violations of copy right through the internet and law enforcement of copy right through the internet. A form of violation of copyright through internet media in the form of violations of the economic rights of creators and copyright holders. The copyright infringement is carried out through two main activities on the internet, namely, uploading and downloading, this activity is carried out in an illegal way without giving rewards or royalties to the creator / license holder. while the law enforcement is considered not optimal. This is due to the many obstacles in its implementation, such as copyright laws that cannot keep pace with developments in technology and information. institutions related to copyright protection have not shown optimal performance. Public legal awareness of the basic concept of copyright is still minimal. This is also based on low economic factors that encourage people to prefer to infringe copyright